2020
DOI: 10.1016/j.jgo.2019.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Obinutuzumab and miniCHOP for unfit patients with diffuse large B-cell lymphoma. A phase II study by Fondazione Italiana Linfomi

Abstract: To evaluate activity and safety of obinutuzumab-miniCHOP (Ga101-miniCHOP) combination in older patients with Diffuse Large B-Cell Lymphoma (DLBCL) unfit to receive full dose immunochemotherapy. Materials and Methods: We conducted a Simon's two-stage phase II multicenter trial to investigate response rate (primary endpoint) and safety of six courses of Ga101-miniCHOP in older patients with DLBCL (≥65 years), prospectively defined as unfit according to a simplified Comprehensive Geriatric Assessment (sCGA). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…[100] Replacing rituximab with the 3 rd -generation antibody obinutuzumab did not improve outcomes. [101] BR is often viewed as palliative, though in a prospective sCGAguided trial focused on frail patients, it resulted in 51% 2-year OS, comparable to 59% observed after R-mini-CHOP. [89] Other studies reported less favorable results for bendamustine combinations, with median OS ≤1 year.…”
Section: Options For Unfit and Frail Patientsmentioning
confidence: 98%
See 1 more Smart Citation
“…[100] Replacing rituximab with the 3 rd -generation antibody obinutuzumab did not improve outcomes. [101] BR is often viewed as palliative, though in a prospective sCGAguided trial focused on frail patients, it resulted in 51% 2-year OS, comparable to 59% observed after R-mini-CHOP. [89] Other studies reported less favorable results for bendamustine combinations, with median OS ≤1 year.…”
Section: Options For Unfit and Frail Patientsmentioning
confidence: 98%
“…R‐mini‐CHOP, R‐CNOP, or R‐GCVP have been recommended by guidelines as viable curative options [100]. Replacing rituximab with the third‐generation antibody obinutuzumab did not improve outcomes [101]. BR is often viewed as palliative, although in a prospective sCGA‐guided trial focused on frail patients, it resulted in 51% 2‐year OS, comparable to 59% observed after R‐mini‐CHOP [89].…”
Section: Management Strategies For Older Patients With Dlbclmentioning
confidence: 99%
“…26 Similar data of efficacy and safety were reported in a phase II trial of Fondazione Italiana Linfomi (FIL) in elderly unfit patients treated with GA101 plus dose-reduced CHOP. 27 Tafasitamab Tafasitamab (MOR208) is an anti-CD19 humanized Ab enhanced by the modification of two amino acids in the Fc region, which increases its affinity for Fcγ receptors. It mediates Ab-dependent cellular phagocytosis, Abdependent cellular cytotoxicity via NK cells, and direct cytotoxicity.…”
Section: Obinutuzumabmentioning
confidence: 99%
“…The median sample size of the studies was 100 (range, 25-869), and the me(di)an age of included patients ranged from 58 to 86 years. Eight studies focused on acute myeloid leukemia and/or myelodysplastic syndromes, [19][20][21][22][23][24][25]27 two on chronic lymphocytic leukemia, 28,29 13 on lymphoma, [30][31][32][33][34][35][36][37][38][39][40][41][42] seven on multiple myeloma, [42][43][44][45][46][47][48] and 15 studies included various hematologic malignancies. [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] The median number of domains addressed in the geriatric assessment was four (range, 2-9).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…median age less than 68 years old, or more than one third of the patients younger than 65 years old); 22,27,41,43,46,48,50,58,59 these studies were assessed as not being fully representative of the target cohort of the average older patients with a hematologic malignancy. Similarly, eight studies focused on a very specific treatment 20,23,24,31,51,55,56,60 which we considered as not fully representative of our target population. Overall, the duration of follow-up was sufficient but in nine studies the followup rate was less than 90% 24,30,46 or the adequacy of followup was not reported.…”
Section: Quality Assessmentmentioning
confidence: 99%